GRAVSYS Software Based on Scratch Programming for 2D Gravity Anomalies Source Responses and Its Implementation in Trangkil Gunungpati - ., Supriyadi; Heparona, Jefta; ., Sugiyanto; ., Mahardika; Kusumawardhani, Rini; Upomo, Togani Cahyadi (KnE Social Sciences, 2019)
Gravsyssoftwarewascreatedwiththeaimtoovercomestudent’sproblemswhichhave difﬁculty in understanding the concept of gravity. This software was developed using Scratch programming which has features to make a simple appearance in the form of images, animations and simulations. Therefore, an innovation of software products can be established as a learning media for students who take gravity method courses. Broadly speaking, Gravsys has several main features, namely data input of parameter model, creating 2D simulation of uniform object, and displays the response of the gravitationalﬁeldanomalyingraphicalform,sothatitcanhelpstudentstounderstand the concept of anomalous source objects and response to gravity anomalies caused by source objects for various subsurface cases, seawater intrusion, water pollution, natural resource potential (coal, iron ore), prediction of bunker existence, decrease and increase of ground water level. In the implementation stage of Ayodya, Trangkil, Gunungpati, the subproject layer showed that 3 layers were sandy clay with density 1,4 gr/cm3, sand with density of 2.3 gr/cm3, bedrock with density 2.6 gr/cm3, each at a depth of 0-30 meters, 30-60 meters, and over 60 meters. Keywords: gravity method, gravity anomaly, Scratch, simulation.